ANALISIS PENGARUH INFLASI TERHADAP TINGKAT PROFITABILITAS BANK MUAMALAT INDONESIA DAN BANK CENTRAL ASIA (BCA) TAHUN 2007-2011 - FAUZIAH, RAVIKA (Jurnal Akuntansi AKUNESA, 2013)
This research is performed in order to test the influence of the variable Inflation ratetoward Return on Asset (ROA), Return On Equity (ROE), and BOPO on BankMuamalat Indonesia and Bank Central Asia at 2007-2011 period. Analysis techniqueused is linear regression which is inflation rate as independent variable and ROA, ROE,BOPO as dependent variable. The result of this research conclude that the inflation rateis not significantly influence Return on Asset (ROA), Return On Equity (ROE), andBOPO.Keyword: ROA, ROE, BOPO, Inflasi.